Consistency in Design: Prediction of the Operative Speed on Roads - Posada, John Jairo; Cadavid Agudelo , Sara; Castro Gómez, Laura (Ingeniería Solidaria, 2014)
Consistency is a concept that is used, among others, to assess road safety, in both the design and operational phases; for example, identifying changes in the operative speed with respect to speed of design along the length of a road. This article presents the concept of consistency in road design and its different approaches, showing the model principles that have been applied and are currently applied according to the speed profile. This is based on the operative speed observed when people drive their vehicles under free-flowing conditions along a road. In order to simplify operative speed prediction models, but without losing sight of the quality of the results, the authors propose to unify various existing models with similar characteristics, obtaining as a result high correlation coefficients that support their validity. They also recommend developing future models applied to Colombian conditions with one lane or bidirectional roadways as well as four-lane ones.